KIOM-79 Prevents Lens Epithelial Cell Apoptosis and Lens Opacification in Zucker Diabetic Fatty Rats. (7th September 2010) - Kim, Junghyun; Kim, Chan-Sik; Sohn, Eunjin; Kim, Hyojun; Jeong, Il-Ha; Kim, Jin Sook
Abstract : Damage of lens epithelial cells (LECs) has been implicated in cataract formation. The aim of this study was to investigate the protective effect of KIOM-79, a combination of four plant extracts, on LECs. We examined the levels of advanced glycation end products (AGEs), nuclear factor-kappaB (NF-κ B) activation and inducible nitric oxide synthase (iNOS) expression in LECs during cataract development using the Zucker diabetic fatty (ZDF) rat, an animal model of type 2 diabetes. KIOM-79 was orally administered by gavage to ZDF rats once a day for 13 weeks. Apoptosis was detected by TUNEL assay, and NF-κ B activation and iNOS expression were studied by southwestern histochemistry and immunohistochemistry, respectively. In diabetic cataractous lenses, TUNEL-positive LECs were markedly increased 20-fold, and AGEs were highly accumulated (2.7-fold) in LECs. In addition, both NF-κ B activation, and iNOS expression were significantly enhanced 3- to 5-fold, respectively, compared to levels found in normal ZL rats. However, the administration of KIOM-79 delayed the development of diabetic cataracts and prevented LEC apoptosis (70%) through the inhibition of AGEs, NF-κ B-activation and iNOS expression. These observations suggest that KIOM-79 is useful in inhibiting diabetic cataractogenesis and acts through an antiapoptotic mechanism to protect LECs from injury.